Evaluating Institutional Frameworks and Regional Disparities in the Utilization of Wastewater Treatment Plant Sludge in Bulgarian Agriculture: A new Institutional Economics Approach - Hrabrin Bachev; Bilal Kargı; Bekir Cihan Uçkaç (Journal of Global Innovations in Agricultural Sciences)
The conversion of sludge from wastewater treatment plants (WTP) into economically valuable agricultural products is shaped by a complex interplay of social, economic, technological, agronomic, and institutional factors. Among these, the institutional framework is a key determinant, influencing the behavior and interactions of stakeholders involved in sludge management. This framework, encompassing both governance institutions and institutional environments, establishes both enabling conditions and limitations that steer stakeholder actions, thereby affecting the efficiency and integration of sludge use in agriculture. This study adopts an interdisciplinary approach grounded in New Institutional Economics to assess the institutional framework that governs the utilization of WTP sludge in Bulgarian agriculture. The analysis reveals substantial progress over the past two decades in the development of regulatory, public, private, market, and hybrid mechanisms, which have led to improvements in sludge application practices. However, the study also identifies regional disparities in the sustainability and pace of development. Understanding the underlying factors that limit stakeholder actions and contribute to these regional variations is essential. To address these challenges, further interdisciplinary research is required, along with a comprehensive evaluation of the institutional framework. This includes gathering both micro- and macro-level data from stakeholders, potentially through official agro-statistical systems at national and EU levels. It is crucial to develop a new national strategy for sludge utilization that aligns with contemporary conditions and societal demands, accompanied by targeted support mechanisms for stakeholders, particularly farmers, using tools such as the Common Agricultural Policy (CAP). Furthermore, investigating institutional frameworks and sludge management practices in other EU countries can provide valuable comparative insights, enabling a more accurate assessment of Bulgaria’s position and informing future policy strategies. Lessons from other nations' experiences can serve as important guidance for management decisions and long-term planning. Keywords: Wastewater treatment plant (WTP), sludge, institutional framework, new institutional economics, agricultural sludge utilization, policy analysis.